2011
DOI: 10.1111/j.1463-6395.2010.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

The non‐hierarchical, non‐uniformly branching topology of a leuconoid sponge aquiferous system revealed by 3D reconstruction and morphometrics using corrosion casting and X‐ray microtomography

Abstract: Hammel, J.U., Filatov, M.V., Herzen, J, Beckmann, F., Kaandorp, J.A. and Nickel M. 2011. The non‐hierarchical, non‐uniformly branching topology of a leuconoid sponge aquiferous system revealed by 3D reconstruction and morphometrics using corrosion casting and X‐ray microtomography. —Acta Zoologica (Stockholm) 00:1–12. As sessile filter feeders, sponges rely on a highly efficient fluid transport system. Their physiology depends on efficient water exchange, which is performed by the aquiferous system. This promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Research into the biomechanics and fluid dynamics of filter-feeding and into biological fluid transport systems in general has revealed a close interdependence between hydrodynamic constraints, the micro- and macro-morphology of the cellular elements involved and, indeed, the structure of the anatomy in its entirety [1] [6] . A number of hydrodynamic constraints and optimality principles have been suggested to play a role in shaping the general architecture of the canal system [3] , but the key features appear to be flow resistance and pressure drop [2] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the biomechanics and fluid dynamics of filter-feeding and into biological fluid transport systems in general has revealed a close interdependence between hydrodynamic constraints, the micro- and macro-morphology of the cellular elements involved and, indeed, the structure of the anatomy in its entirety [1] [6] . A number of hydrodynamic constraints and optimality principles have been suggested to play a role in shaping the general architecture of the canal system [3] , but the key features appear to be flow resistance and pressure drop [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The morphometric and anatomical data pertaining to the architecture of the canal system and the cell types involved then needs to be integrated into basic fluid dynamic theory in order to gain a deeper and more detailed understanding of the hydrodynamic situation as a whole in sponge canal systems. Current understanding is based on general information regarding leucon-type canal systems [3] , [4] , [9] , [10] and recent specific morphometric and hierarchical data pertaining to the aquiferous system [6] . Flow velocity within the canal system is affected most prominently by the total available cross-sectional area of every functional unit in it ( Figure 1A–C ) [3] , [4] , [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger particles (such as yeasts, flagellates, and other small eukaryotes) are possibly retained along the inhalant and exhalant canals or by the outer surface of the choanocyte chambers, while bacteria are likely entrapped by the choanocytes (Langenbruch, ; Weissenfels, , ; Willenz, ; Willenz & Van de Vyver, ). In addition, some of these larger particles may not be engulfed in the canals, exiting the body of the sponge possibly by bypasses in the aquiferous system (Bavestrello, Arillo, Calcinai, & Cerrano, ; Bavestrello, Calcinai, Boyer, Cerrano, & Pansini, ; Hammel et al, ; Hammel & Nickel, ; Ludeman et al, ). It will be important to investigate the architecture of the aquiferous system of this species either using corrosion casts (e.g., Bavestrello et al, ), micro CT‐Scanning (Hammel et al, ), or by 3D reconstruction from serial sections (e.g., Brenzinger, Padula, & Schrödl, ; Leys, Zaman, & Boury‐Esnault, ) to better comprehend the water path in this species.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 years later, this statement is still valid. Even though much advancement were achieved in investigating the three‐dimensional architecture of some species (Bavestrello et al, , ; Hammel et al, ), there are still several questions on the organization and function of the main characteristic of the sponges (Leys & Hill, ). Here, we demonstrated that the investigated specimens of C. caelum were repent, having their oscula aligned at their apical portion of their body.…”
Section: Discussionmentioning
confidence: 99%